2006
DOI: 10.1002/hed.20523
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantitative assessment of oral tongue cancer by intraoral ultrasonography

Abstract: Intraoral ultrasonography in conjunction with the proposed CAD system allows tissue characterization and prediction of subclinical cervical lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
(34 reference statements)
0
40
0
1
Order By: Relevance
“…UTT was the most widely reported metric and was assessed in 10 of the 19 studies . The ability to accurately T stage tumors using dimensions obtained during sonographic examination was also investigated by two of the 19 studies Classification of deep margin shape was also used as a method to study different patterns of invasion by three studies . The categories used to describe different margin shapes, however, varied significantly across the three studies.…”
Section: Resultsmentioning
confidence: 99%
“…UTT was the most widely reported metric and was assessed in 10 of the 19 studies . The ability to accurately T stage tumors using dimensions obtained during sonographic examination was also investigated by two of the 19 studies Classification of deep margin shape was also used as a method to study different patterns of invasion by three studies . The categories used to describe different margin shapes, however, varied significantly across the three studies.…”
Section: Resultsmentioning
confidence: 99%
“…US can be used as a preoperative noninvasive tool with which to assess the histological structure of tongue cancer [2,[5][6][7][8][9][10][11][12][13][14]. Hayashi [15] reported that US should be routinely used as a standard technique to evaluate the depth of tumor invasion.…”
Section: Discussionmentioning
confidence: 98%
“…Preoperative ultrasonography (US) assessment is useful to noninvasively predict the prognosis of tongue cancer [2,3]. Some reports have demonstrated the usefulness of intraoral US for delineating the shape of the tumor margin, internal echo signal, tumor extent, and depth of invasion [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. US images reflect the histological structure of tongue cancers, even superficial carcinomas [2,[5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Tumour thickness on intraoral ultrasonography images is reportedly an important predictor of cervical lymph node metastasis and patient outcome. [4][5][6][7][8] Invasion front ratio calculated from the length of the invasive front on intraoral ultrasonography images is related to the histopathological grade.…”
Section: Introductionmentioning
confidence: 99%